Ninth Five Year Plan Tamil Nadu 1997-2002 an Outline - Planning Commission (Planning Commission, 1997)
The people of Tamil Nadu have exhibited through democratic process, the desire and need for a change - change for a better alternative development model. This model should be so designed that it meets various aspirations of the people. This means the development plan of the State has to be re-oriented to enable everyone to have access to Basic Minimum Needs, like food, clothing, shelter, drinking water, health, education etc., and to reduce the levels of poverty and unemployment. The responsibilities of the State need to be incorporated in the future plans to provide safety net for the poor and the under privileged. the State Government will discharge its developmental responsibilities in a federal structure. Therefore, the need for getting better share for the State in the federal finance will be of paramount importance in the developmental Plan efforts.
State Planning Commission Tamil Nadu